Modulus-based matrix splitting methods for horizontal linear complementarity problems - Mezzadri, Francesco; Galligani, Emanuele (Numerical algorithms, 2020)
In this paper, we extend modulus-based matrix splitting iteration methods to horizontal linear complementarity problems. We consider both standard and accelerated methods and analyze their convergence. In this context, we also generalize existing results on modulus-based matrix splitting iteration methods for (non-horizontal) linear complementarity problems. Lastly, we analyze the proposed methods by numerical experiments involving both symmetric and non-symmetric matrices.